Pengaruh Budaya Organisasi, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Pegawai ( Studi Pada Pegawai Kantor Kecamatan Puspo Pasuruan) - Nova Dwi Cahyani; Hadi Sunaryo; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractTo determine the influence between organizational culture, work motivation, and job satisfaction. This research was conducted on 35 respondents. The data analysis technique used multiple linear regression.The results of descriptive analysis in this study indicate that employees of the Pasuruan Puspo District Office perceive all research, namely organizational culture, work motivation, job satisfaction and employee performance. Organizational culture, work motivation, and job satisfaction simultaneously influence the performance of the employees of the Puspo Pasuruan District Office. Keywords: Organizational Culture, Work Motivation, Job Satisfaction, and Employee Performance.